Opening Marine Long-Term Ecological Science: Lesson Learned From the LTER-Italy Site Northern Adriatic Sea - Minelli, Annalisa; Sarretta, Alessandro; Oggioni, Alessandro; Bergami, Caterina; Bastianini, Mauro; Bernardi Aubry, Fabrizio; Camatti, Elisa; Pugnetti, Alessandra (Frontiers in Marine Science, 2021)
This work presents a practical case study of the Open Science principles applied to the valorization of a long-term marine dataset collected in the Northern Adriatic Sea, one of the Long-Term Ecological Research (LTER) sites of the LTER-Italy network. The dataset covers a temporal range of 50 years (1965–2015), and it is composed of abiotic, and phyto- and zooplankton data, for a total of 21 parameters. The case study involved many actions, which will be described here, distinguishing between the ones affecting the whole research project workflow and those acting more specifically on the dataset. We evaluate strengths, weaknesses, and possible improvements for each action. The present study pointed out that, despite the initial and still some remaining mistrust, opening research projects is more than a best practice. It is (i) important because it improves research transparency (increasing researchers’ credibility, replicability of science, and products reuse), (ii) required by many international initiatives and regulations, and (iii) enriching because it encourages cooperation between scientists across different fields and laboratories.